2016
DOI: 10.2147/copd.s119992
|View full text |Cite
|
Sign up to set email alerts
|

Persistent disabling breathlessness in chronic obstructive pulmonary disease

Abstract: ObjectiveTo determine the prevalence, change in breathlessness status over time, and risk factors for disabling and persistent disabling breathlessness in relation to treatments in chronic obstructive pulmonary disease (COPD).Materials and methodsLongitudinal analysis of data from the Swedish National Register of COPD with breathlessness measured using modified Medical Research Council (mMRC) scores at two subsequent visits. Prevalence of disabling breathlessness (mMRC ≥2 at baseline) and persistent disabling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Interestingly, triple therapy was most common in all GOLD groups apart from group A in 2014 and was also the second most common alternative in group A. We speculate that the widespread use of triple inhaled therapy is due to the chronic characteristic of the disease, with a documented high proportion of persistent breathlessness in spite of maximum optimized treatment [25]. Other potential explanations may be increased availability of inhaled therapy in different devices and combinations, overtreatment due to heavy marketing from drug companies, and increased awareness and implementation of GOLD ABCD recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, triple therapy was most common in all GOLD groups apart from group A in 2014 and was also the second most common alternative in group A. We speculate that the widespread use of triple inhaled therapy is due to the chronic characteristic of the disease, with a documented high proportion of persistent breathlessness in spite of maximum optimized treatment [25]. Other potential explanations may be increased availability of inhaled therapy in different devices and combinations, overtreatment due to heavy marketing from drug companies, and increased awareness and implementation of GOLD ABCD recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the deterioration in HRQoL of the non-participants did not reach minimally clinical important difference of 0.4 [20], it was found that the non-participants deteriorated while the participants improved. In a register study of patients affected by COPD, disabling breathlessness, defined as an mMRC score ≥2, was found in 54% of the patients, and predictors of disabling breathlessness were found to be higher age, lower FEV 1 % of predicted values, obesity, and depression [7]. Dyspnea could be detrimental to well-being.…”
Section: Discussionmentioning
confidence: 99%
“…When adjusting for spirometric stage of COPD, deteriorated HRQoL was found to be predicted by increasing dyspnea, depression/anxiety, an increasing number of exacerbations, and decreased exercise capacity [6]. Other signs of deteriorating COPD disease are disabling breathlessness [7] and low body mass index [8]. …”
Section: Introductionmentioning
confidence: 99%
“…These patients had end-stage COPD with chronic respiratory failure with a median survival time of 1.9 years 4. Breathlessness is very common in patients with very severe COPD5 and a high proportion of patients suffer from chronic breathlessness, despite intensive COPD treatment 6. In a recent study of less severely ill COPD patients, chronic breathlessness that significantly compromised function was present in 74% of patients, despite combined inhaled triple therapy and physiotherapy 6.…”
mentioning
confidence: 99%
“…Breathlessness is very common in patients with very severe COPD5 and a high proportion of patients suffer from chronic breathlessness, despite intensive COPD treatment 6. In a recent study of less severely ill COPD patients, chronic breathlessness that significantly compromised function was present in 74% of patients, despite combined inhaled triple therapy and physiotherapy 6. Given the evidence base for the efficacy of low-dose opioids for safely reducing chronic breathlessness, our finding that only 2% of opioid prescriptions were for breathlessness strongly supports the assertion that there is systematic undertreatment of people with chronic breathlessness and advanced COPD.…”
mentioning
confidence: 99%